Investigating the Relationship between Locus of Control, Emotional Intelligence, and Resilience among Young Male Opium Abusers in Shiraz - Bahareh Zeynalzadeh Ghoochani; Seyed Alireza Derakhshanrad; Mohammad Ahmadpour (Shiraz University of Medical Sciences, 2022)
Background: Addiction destroys lifestyles and affects individuals, family,and society. The present study aimed to investigate the relationship between resilience, locus of control, and emotional intelligence in opium addicts.Recognizing the weaknesses of this group helps them to recover and can provide preventive strategies for society.Methods: A total of 40 male opium addicts were selected by convenience sampling from Ibn-e-Sina Center in Shiraz. Rotter, Shrink, Connor-Davidson,and demographic questionnaires were used in this cross-sectional study, and Pearson's test was used to obtain the correlation coefficient.Results: Less resilient people reported more relapses after quitting (r=-0.424,P=0.006). People with higher social awareness used psychological therapies to liberate themselves from addiction (r=0.337, P=0.033). Longer addiction was reported among people who consumed opium more frequently during the day (r=0.433, P=0.005). Greater frequency of daily consumption and more years of consumption had a positive relationship with increasing the number of quits and relapses (r=0.323, P=0.042; r=0.362, P=0.022).Conclusion: Addiction treatment centers should evaluate and improve the levels of resilience, emotional intelligence, and type of locus of control in addicts. Most of the participants started their addiction out of curiosity between the ages of 20 and 25 years. The media and policymakers are recommended to play a vital role in raising social awareness and clarifying the devastating consequences of opium addiction. Most of the participants were unemployed and needed money for more treatments. Therefore, it is advisable that rehabilitation centers use occupational therapists for pre-vocational and vocational rehabilitation programs in the treatment process.